The Effect of Giving “Semundu” Juice with a Combination of Probiotics on Blood Pressure in Pre-Hypertension Patients - Septia, Reka; Maigoda, Tonny C; Krisnasary, Arie; Hariadi, Hari (Research and Social Study Institute, 2024)
Hypertension is a medical condition characterized by elevated blood pressure beyond normal limits. Management strategies for hypertension can be pharmacological or non-pharmacological. This study aims to evaluate the effect of administering